Delay Factors in Reconstruction Projects: A Case Study of Mataf Expansion Project - Al Khatib, Basem; Yap, Soon Poh; El-Shafie, Ahmed (MDPI, 2018)
Delays in construction projects are a common phenomenon throughout the industry. This problem has many negative impacts on the time, cost, and sustainability of the projects. Many studies were conducted to identify the main causes of this delay in new construction projects in different regions but very few studies have focused on finding an explanation for the causes of delay in major reconstruction projects that have great religious and cultural sustainability. This paper examines the factors that contributed to work delays in one of the most major reconstruction projects that took place recently in the Middle East, which is namely the Mataf Expansion Project in the city of Mecca, Saudi Arabia. Fourteen interviews were conducted with project managers, construction managers, and senior site engineers to identify the factors that they encountered and led to the delay in the reconstruction activities of this project. Some of the findings were consistent and similar to most other causes of delay that are associated with new construction projects. However, interestingly, this research has discovered the existence of other unavoidable factors that caused a delay and should be considered for any similar reconstruction projects. The results showed that these factors could be divided into two groups: the first one is related to the demolition phase (five factors) and the second group is related to construction works (nine factors). In addition, it has been observed that the building material during the reconstruction is considered one of the major delaying factors. Finally, these 14 delay factors should be carefully considered to assure the sustainability of the main object's function during the reconstruction activities.